2020
DOI: 10.1111/dth.13306
|View full text |Cite
|
Sign up to set email alerts
|

Could vascular endothelial growth factor inhibitors induce hidradenitis suppurativa? Report of three patients with renal cancer treated with sunitinib

Abstract: Hidradenitis suppurativa (HS) is a chronic autoinflammatory skin disease that primarily affects hair follicles. 1 Up to date, its pathogenesis remains unclear. Drug-induced cases of HS have been described with some treatments such as rituximab, lithium, and vemurafenib. 2 Skin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Derek J et al recently reported that HS keratinocyte exhibited a significant lower level of VEGF, as well as IL-1α and IL-22 compared to normal keratinocyte using an in-vitro scratch assay, suggesting that changes in VEGF signaling may be associated with HS pathogenesis [ 119 ]. Furthermore, there was a case report that showed that sunitinib reactivates, worsens or triggers HS during treatment of a patient’s underlying cancer [ 120 ]. The association between HS and angiogenesis is still not well known, and further studies are needed in this area.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%
“…Derek J et al recently reported that HS keratinocyte exhibited a significant lower level of VEGF, as well as IL-1α and IL-22 compared to normal keratinocyte using an in-vitro scratch assay, suggesting that changes in VEGF signaling may be associated with HS pathogenesis [ 119 ]. Furthermore, there was a case report that showed that sunitinib reactivates, worsens or triggers HS during treatment of a patient’s underlying cancer [ 120 ]. The association between HS and angiogenesis is still not well known, and further studies are needed in this area.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%